DISCOURSE AGAINST CONSUMERISM AND THE QUEST FOR FREEDOM IN THE FILM FIGHT CLUB - Phisit Rojkanarach (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research examines the film Fight Club by David Fincher, adapted from novel Fight Club by Chuck Palahniuk, to find out how conflicts between consumerism and characters’ quest for freedom are resolved. The concepts and theories employed in the analysis of the film are the theory of freedom, psychoanalysis, and film analysis. The analysis reveals that anti-consumerism is the main theme of the film as conveyed through the use of symbols and characterization. Consumerist society makes the characters suffer so they want to be free from it and find a place where they belong. Therefore, they have founded Fight Club, a space that initially provides them an escape from mainstream hegemony by means of violence. However, freedom gained by violence is not true freedom. In order to be truly free, people have to acquire self-realization, self-mastery and be satisfied with who they are. Significantly, to know the self, it is important to acknowledge one’s limitations and strengths. Thus, the researcher hopes that the findings of this research can provide a hint of the way to freedom for individuals and society.